Semi-conditional cash transfers in the form of family allowances for children and adolescents in the informal economy in Argentina - Bertranou, Fabio (2012)
In 2009, Argentina introduced a new transfer programme for children and adolescents younger than age 18 (Universal Child Allowance) that extended coverage under the contributory programme for family allowances to include families in the informal economy and families of unemployed persons. This article describes this innovative programme, compares it with similar programmes in Latin America and analyses its impact on coverage and its possible effects on the welfare of the population. The results indicate that the extension of access to this type of benefit has reduced considerably the coverage gap for the poor and indigent and supports efforts to consolidate the operations of different and poorly coordinated transfer programmes.